A comprehensive review of research on organic-based phase-change thermal interface materials for thermal management of electric devices: Methods, performance, and applications - Wondu Lee; Jooheon Kim (Polymer Testing)
Efficient thermal management is crucial for the optimal performance and longevity of electronic devices. With continuous advancements in technology and the ongoing miniaturization of electronic components, the requirement for effective heat-dissipation materials has become increasingly imperative. In this regard, organic phase-change materials (PCMs) have emerged as promising candidates for thermal management applications due to their unique properties. This paper explores the utilization of organic PCM-based heat dissipation materials for electronic devices, aiming to enhance their thermal performance and reliability. Through a comprehensive review of recent research and developments in this field, the paper discusses the fundamental principles underlying the thermal properties of organic PCMs and their suitability for electronic applications. The paper also discusses the challenges and opportunities associated with the integration of organic PCM-based materials into electronic devices, emphasizing the importance of addressing issues such as material compatibility, durability, and scalability. Overall, this review provides valuable insights into the utilization of organic PCM-based materials as efficient heat dissipation solutions for electronic devices, contributing to the advancement of thermal management technologies in the electronics industry.